A statistical survey of the composition of gallstones in eight countries - Sutor, D. June (1971)
The crystalline composition of gallstones from Australia, England, Germany, India, Kuwait, South Africa, Sweden, and the USA has now been determined by the x-ray powder method. Eleven compounds were identified. The three cholesterols—cholesterol monohydrate, anhydrous cholesterol, and cholesterol II—account for 71% of the total crystalline material in the stones; the calcium carbonates—vaterite, aragonite, and calcite—contribute 15%, and calcium palmitate contributes 6%. Smaller amounts of apatite, sodium chloride, whitlockite, and α-palmitic acid were also found. The composition distribution in each country is significantly different. Gallstones from Germany, Sweden, and Australia are the most similar. Gallstones from England have significantly more carbonate, and stones from South Africa have much less cholesterol and more calcium phosphate and calcium palmitate. Stones from Kuwait have a large amount of calcium palmitate and those from India an excess of calcium phosphate. The composition of stones related to the age and to the sex of a patient shows that although there are no significant differences in composition for patients under and over the age of 50 there are differences in the stone composition related to the patient's sex. Female patients form much more cholesterol while males form much more calcium palmitate and slightly more calcium carbonate. The differences also exist for female and male patients over and under 50 years of age. A study of the texture and orientation of the crystalline material in the gallstones has shown that anhydrous cholesterol and cholesterol monohydrate can occur as single crystals oriented with respect to the nucleus whereas other stone components are disoriented crystallites.